The Solution:
Given the explicit rule of a sequence below:
![a_n=9-14n](https://img.qammunity.org/2023/formulas/mathematics/college/ztihkh54tcw1znu2rgqjkmywxgvmmcv6n3.png)
We are required to determine the recursive rule for the sequence.
Step 1:
Find the first term, that is, when n=1.
![\begin{gathered} a_1=9-14(1)=9-14=-5 \\ \\ a_1=-5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/x0fvfcatf4kefnod2qyd4q8fzjc1rrdsfj.png)
Step 2:
Find the second to the last term, that is, when n=n-1.
![a_(n-1)=9-14(n-1)=9-14n+14=9+14-14n=23-14n](https://img.qammunity.org/2023/formulas/mathematics/college/hzkxsyxwrn567nzgdah4a5kq95ul2bx60y.png)
Step 3:
Find the d, the common difference.
![\begin{gathered} d=a_n-a_(n-1)=9-14n-(23-14n)=9-14n-23+14n \\ \\ d=9-23-14n+14n=-14 \\ \\ d=-14 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/j0ms3pbx6kogttpsc3p7dh707376fyjyai.png)
Recall:
The recursive rule for a linear sequence is:
![a_n=a_(n-1)+d](https://img.qammunity.org/2023/formulas/mathematics/college/amblrzzydktrclf12rsmm7k1m3myhwksid.png)
Substituting -14 for d, we get
![a_n=a_(n-1)-14](https://img.qammunity.org/2023/formulas/mathematics/college/n9z8dtsd98qp75iluxhzje0wn61zaran2e.png)
Thus, the recursive rule for the sequence is:
![\begin{gathered} a_(n)=a_(n-1)-14 \\ \\ a_1=-5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ymdciudu6nhepri56x3rhwequ24ahyxf9v.png)
Therefore, the correct answer is [option 3]